Colloidal synthesis of MoSe2 nanonetworks and nanoflowers with efficient electrocatalytic hydrogen-evolution activity. (20th March 2017) - Guo, Weibin; Chen, Yuanzhi; Wang, Laisen; Xu, Jin; Zeng, Deqian; Peng, Dong-Liang
Abstract: MoSe2 represents an important layered transition metal dichalcogenides (LTMDs) that have high electrocatalytic activity in hydrogen evolution reaction (HER). A key issue to achieve excellent electrochemical properties of MoSe2 is to synthesize nanostructures that are composed of few-layer MoSe2 with maximized exposure of active edge sites. In this study, we report the synthesis of MoSe2 nanostructures with network-like and flower-like morphologies via an organic solution approach that utilizes molybdenum hexacarbonyl as Mo precursor and Se powders as Se source. The prepared MoSe2 nanostructures consist of few-layer ultrathin nanosheets which can have different orientations. Depending on the volume ratio of oleylamine to oleic acid, the arrangement of ultrathin MoSe2 nanosheets is adjustable and can form porous network-like or discrete flower-like nanostructure which has large specific surface area and a wealth of exposed edge sites. Excellent HER activities with low overpotentials, small Tafel slopes and long-term durability are observed on the as-synthesized MoSe2 nanostructures. The acetic acid-washing step that may effectively remove the organic molecules capped on MoSe2 surfaces is also found to be efficient in improving the HER activity of the synthesized MoSe2 nanostructures.